Comparison of two training techniques (mannequin versus flip-chart presentation) of breast self examination of rural women: An interventional study. (March 2018) - Raithatha, Shyamsundar J.; Mangalampalli, Anusha; Patel, Manishkumar; Kumar, Dinesh; Tapadiya, Mahima
Highlights: The mannequin based training led to a higher increase in the knowledge, attitude and practice scores as compared to the flip-chart based training but the difference was not statistically significant. The knowledge about risk factors for breast cancer was present in around half of the women which is appreciable considering the rural setting. The most common reason reported for not performing BSE was not being aware of BSE. Abstract: Breast self-examination (BSE) is an important component of any program for the early detection of breast cancer. The present study aimed to evaluate the effectiveness of the mannequin based approach on BSE practices through a community based quasi-experimental study with a control group. A sample size of 109 rural women was selected for the interventions. Data was collected using an interview schedule before and after the interventions. The knowledge about risk factors for breast cancer was present in around half of the women which is appreciable considering the rural setting. Some misconceptions were present as well. Two third of the participants accepted that BSE is important for them, about one third of the women believed that they will be able to perform BSE effectively and only one-fourth had ever done BSE in their life time. The most common reason reported for not performing BSE was not being aware of BSE. The mannequin based training led to a higher increase in the knowledge, attitude and practice scores as compared to the flip-chart based training but the difference was not statistically significant.